1996
DOI: 10.1177/0148607196020002123
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Symptoms Due to Possible Chromium Deficiency in Long‐Term Parenteral Nutrition That Closely Mimic Metronidazole‐Induced Syndromes

Abstract: Neuropathy and glucose intolerance may occur despite increased serum chromium levels and respond to chromium infusion. The previous use of drugs such as metronidazole should not exclude chromium as a potential treatment for neuropathy in HPN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Acute beriberi with severe thiamine deficiency has been reported and can be life threatening [61]. Iron deficiency anemia is common with TPN [62], and clinically significant sequelae can be seen with deficiencies of selenium [63], copper [64], zinc [65], and chromium [66]. Conversely, trace element toxicity can have serious effects, as with manganese neurotoxicity, which may develop with concomitant cholestatic liver disease [67], and aluminum-related bone disease, as described previously.…”
Section: Other Metabolic Disordersmentioning
confidence: 89%
“…Acute beriberi with severe thiamine deficiency has been reported and can be life threatening [61]. Iron deficiency anemia is common with TPN [62], and clinically significant sequelae can be seen with deficiencies of selenium [63], copper [64], zinc [65], and chromium [66]. Conversely, trace element toxicity can have serious effects, as with manganese neurotoxicity, which may develop with concomitant cholestatic liver disease [67], and aluminum-related bone disease, as described previously.…”
Section: Other Metabolic Disordersmentioning
confidence: 89%
“…Another case study by Verhage et al (1996) reported on a 40-year-old man who had undergone multiple intestinal resections over 11 years, as a result of Crohn's disease, and received TPN for six months while recovering from an injury to the bowel. The TPN solution was reported to provide 5 µg/day of chromium with an estimated additional 2.4-10.5 µg/day of chromium by contamination from the component solutions (Ito et al, 1990).…”
Section: Deficiencymentioning
confidence: 99%
“…Extreme signs of Cr deficiency observed in patients on TPN also include neurologic disorders. Chromium is now routinely added to TPN solutions but may not be adequate under stress conditions since neuropathy of a patient on TPN, who was also receiving metronidazole, was reversed by further addition of Cr to the TPN solutions [14].…”
Section: Dietary Chromium Intake Requirement and Signs Of Deficiencymentioning
confidence: 99%